Back to the Roots? The Applications of Communication Science Theories in Strategic Communication Research. Issue 1 (1st January 2020) - Lock, Irina; Wonneberger, Anke; Verhoeven, Piet; Hellsten, Iina
ABSTRACT: Recently, the field of strategic communication has been criticized for lacking a coherent theoretical synthesis. Recognizing that strategic communication is a sub-discipline of communication science, we study how the field is anchored in the corpus of established communication theories – including social science, interpretative, and critical approaches. To describe the use, development, and context of communication theories in strategic communication publications, we analyzed all articles published in ten public relations/ corporate communication/ organizational communication/ strategic communication journals over twenty years ( N = 4, 027). While the vast majority of articles did not refer to one of the 91 communication theories, the share of references to these theories has been increasing. Overall, we found a high diversity of approaches – with considerable differences among journals – indicating a broad discourse. However, we also found a growing relevance of the social science paradigm. We argue that a stronger focus on communication theories may facilitate a consilient synthesis and increase the relevance of the field, academically and practically. We therefore propose to strengthen the communication science perspective in strategic communication.